2011
DOI: 10.1542/peds.2010-2742
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Taking Behaviors of Adolescents With Extreme Obesity: Normative or Not?

Abstract: OBJECTIVE: Present first published data detailing high-risk behaviors of adolescent high school students (HSS) with extreme obesity (BMI ≥ 99th percentile for age and gender) compared with healthy weight peers (5th–84th percentile). METHODS: The 2007 Youth Risk Behavior Survey was used to compare HSS with extreme obesity (N = 410) and healthy weight peers (N = 8669) in their engagement in (1) tobacco use, (2) alcohol/other dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 61 publications
5
53
1
Order By: Relevance
“…Although some investigators have found positive associations between these risk behaviors and obesity (Sansone, Sansone & Fine, 1995;Shan, et al 2010), other studies found no such association. As Ratcliff, Jenkins, Reiter-Purtill, Noll and Zeller (2011) recently observed, the rates obtained by obese adolescents for the majority of risk behaviors, were similar to those of their normal weight peers.…”
Section: Introductionsupporting
confidence: 80%
“…Although some investigators have found positive associations between these risk behaviors and obesity (Sansone, Sansone & Fine, 1995;Shan, et al 2010), other studies found no such association. As Ratcliff, Jenkins, Reiter-Purtill, Noll and Zeller (2011) recently observed, the rates obtained by obese adolescents for the majority of risk behaviors, were similar to those of their normal weight peers.…”
Section: Introductionsupporting
confidence: 80%
“…This is the first large study to demonstrate an even greater burden of poor weight-related beliefs and unhealthy dieting behaviors for young people with severe obesity, compared to overweight and obese young people. Among severely obese young people, an increased risk of smoking was also found in previous studies [72]. The reasons are still unclear -possible reasons are 'smoking for weight loss' or being 'in'.…”
Section: Risk Behaviors In Adolescents With Extreme Obesitysupporting
confidence: 52%
“…In the WHO computer program, weight-for-age is not calculated beyond 10 years of age, making it harder to determine which outliers for zBMI data are from weight data in adolescents. The BIV cut-offs suggested by the WHO for calculation of zBMI may be too conservative and be incorrectly excluding those patients with extremely high zBMIs 29. One previous study demonstrated the BIV cut-offs from the WHO underestimated obesity prevalence30 and recently, the Center for Disease Control (CDC) changed their upper limit for BIVs from >+5 to >+8 31.…”
Section: Discussionmentioning
confidence: 99%